Tribological behavior of in situ fabricated graphene–nickel matrix composites. Issue 39 (15th June 2018) - Lei, Yu; Jiang, Jinlong; Bi, Tiantian; Du, Jinfang; Pang, Xianjuan
Abstract : Graphene protects nickel from severe oxidation and forms carbon-rich tribofilms containing disordered amorphous carbon and ordered polymers by tribo-chemical reactions. Abstract : Graphene–nickel (G–Ni) composites were in situ fabricated by a powder metallurgy method. The effects of graphene content on the tribological behavior of G–Ni composites were investigated. The tribochemistry and structural evolution of graphene were analyzed by X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy to understand the lubricating role of graphene in the G–Ni composite. The results show that graphene protects the nickel matrix from severe oxidation at the expense of its oxidation during sliding friction. Graphene on the friction interface transforms from a structure with less defects to a disordered amorphous structure. Polymeric segments are also generated by the tribochemical reactions of graphene. The formation of the tribofilms containing amorphous carbon and polymers is responsible for the self-lubricating behavior of the G–Ni composites.